2019
DOI: 10.1136/bmjopen-2018-026797
|View full text |Cite
|
Sign up to set email alerts
|

The COMET (Comparison of Operative versus Monitoring and Endocrine Therapy) trial: a phase III randomised controlled clinical trial for low-risk ductal carcinoma in situ (DCIS)

Abstract: IntroductionDuctal carcinoma in situ (DCIS) is a non-invasive non-obligate precursor of invasive breast cancer. With guideline concordant care (GCC), DCIS outcomes are at least as favourable as some other early stage cancer types such as prostate cancer, for which active surveillance (AS) is a standard of care option. However, AS has not yet been tested in relation to DCIS. The goal of the COMET (Comparison of Operative versus Monitoring and Endocrine Therapy) trial for low-risk DCIS is to gather evidence to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
147
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(150 citation statements)
references
References 64 publications
1
147
0
2
Order By: Relevance
“…To our knowledge, to date there is no empirical evidence that surgical treatment of DCIS reduces the subsequent mortality from breast cancer. Studies that offer a watch and wait approach, such as the Comparison of Operative versus Monitoring and Endocrine Therapy trial, 7 focus on patients with low-risk DCIS and have too few patients to evaluate mortality differences between those who undergo surgical treatment and those who do not. Given the similar SMRs for women with mastectomy and those with lumpectomy, it is possible that the mortality for women who had neither form of surgical treatment would be similar to these.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, to date there is no empirical evidence that surgical treatment of DCIS reduces the subsequent mortality from breast cancer. Studies that offer a watch and wait approach, such as the Comparison of Operative versus Monitoring and Endocrine Therapy trial, 7 focus on patients with low-risk DCIS and have too few patients to evaluate mortality differences between those who undergo surgical treatment and those who do not. Given the similar SMRs for women with mastectomy and those with lumpectomy, it is possible that the mortality for women who had neither form of surgical treatment would be similar to these.…”
Section: Discussionmentioning
confidence: 99%
“…The anxiety of nonoperative management of DCIS stems from known sampling error on core biopsy with pathologic upstaging rates ranging from 10% to 30% at the time of operation. 2,12 Although nonoperative treatment of non-high-grade DCIS is being explored in randomized clinical trials in Europe and the US (eg LORD [Low Risk DCIS], 13 LORIS [Low Risk DCIS], 14 and COMET [Comparison of Operative to Monitoring and Endocrine Therapy for Low-Risk DCIS] trials), 15 these trials are enrolling highly selected patients and have yet to report their results. In addition, retrospective data have shown that in patients meeting LORIS criteria, upstage rates at the time of operation might be 7% to 20%.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the identification of invasion in a patient originally diagnosed with DCIS who has been undergoing AS for 2 years requires an algorithmic approach to Medicare analysis because it is not reported in SEER and cannot be directly observed in SEER-Medicare. These limitations may be addressable with data from ongoing studies aimed at determining whether some DCIS patients with fewer comorbidities may safely opt for AS 22 .…”
Section: Discussionmentioning
confidence: 99%